AN EXPLORATORY STUDY OF PHYSICAL ACTIVITY AND SPORTS ENGAGEMENT AMONG GEN Z PARTICIPANTS IN MODUL NUSANTARA INBOUND RELATED TO PSYCHOSOCIAL DIMENSIONS: A FOLLOW-UP REVIEW - Mulyawan, Rizki; Haratri, Brigita Ratih Kusuma; Putri, Salva Almayda; Maulana, Vistor Syapri; Delano, Enggista Hendriko; Sumaryanti, Sumaryanti; Mohd Nur, Mohad Anizu (MEDIKORA, 2024)
The aim of this study was to investigate the relationship between the active personality habits of student exchange in the Modul Nusantara movement toward their level of participation in sports and the risk of psychological impacts during the inbound activity. This study did not include a review of the Modul Nusantara activity process and lectures based on scientific areas. Methods: This study utilises a quantitative descriptive research design, combining two methods: survey and bibliometric analysis. The primary goal is to identify barriers in engaging in sports among specific students who participate in the Modul Nusantara activity. The participants were selected from a list of 99 student populations. These students were accepted by Universitas Negeri Yogyakarta to participate in student exchanges under the MBKM program, which is facilitated by the PMM scheme administered by the Ministry of Education, Culture, Research and Technology. Participants were selected using a population of 85 individuals, including 37 males and 48 females, who voluntarily participated part in generating the information.  The study used questionnaires to assess motives engaging sports activity through exercise barrier questionnaires, as well as bibliometric measurements using digital learning media to verify the effects of obstacle activities on stress, depression, and anxiety levels. Data measurement analysis is conducted using descriptive statistical tests and calculation formulas that are based on the measurement category approach of each instrument, with a particular focus on the psychosocial element. Additional investigation into the association between variables related to barriers to physical activity, in connection to mental factors, including sub-indicators such as depression, anxiety, and stress. Results:  Distinct findings from the distribution of perception to the exercise motive questionnaire revealed that most participants expressed disagreement with the statements in the instrument. However, the second highest response, particularly among inbound students, demonstrated agreement with the 12 indicators of challenge motivations in exercise. Psychosocial aspect data revealed a leftward trend in the distribution of responses. Each question item reflects the individual's condition, with answers indicating experiences at a certain level or throughout a certain period of time, some time, or experiences that do not apply to the subject at all. A thorough investigation of each item related to the correlation between barrier to exercise and psychosocial aspects revealed that variables such as lack of a preferred exercise location in close location, unfamiliarity with the nearest exercise facility, living at a considerable distance from colleagues, a far-off exercise location, preference for activities besides exercise, laziness, lack of motivation to exercise, and insufficient time or minimal time allocation for exercise exhibit a strong correlation (r>0.05; p: <0.05) and a very powerful correlation (r>0.05; p: <0.01) with dimensions of depression, anxiety, and stress. At the same time, weather conditions are strongly correlated with depression and stress. Additional variables, plenty of college assignments (r: 0.298 > 0.05; p: 0.006 <0.05) and insufficient time for physical exercise (r: 0.355 > 0.05; p: 0.000 <0.01) are strongly and significantly associated only with anxiety. In contrast to other variables, lack of exercise among friends and family members proved to be rather unsatisfactory in terms of depression, anxiety, and stress. In conclusion, Objectives xdriving physical activity and exercise among students participating in the Modul Nusantara strongly associated with the likelihood of developing depression, anxiety, and stress. This, in turn, can lead to a decrease in the willingness to engage in physical activity, therefore reducing the chance of impaired immunity associated with mental illnesses.  More extensive study will be expected to explore in greater depth about the ratio of lectures load during inbound in each inbound students, possibilities for physical activity and recreation, and more thorough psychological factors.